Carlota de Benito Moreno: The Middle Voice and Connected Constructions in Ibero-Romance. A variationist and dialectal account. Amsterdam/Philadelphia: John Benjamins, 2022, 375 pp. ISBN: 978-90-272-1142-2 - Fábregas Alfaro , Antonio (Philologia Hispalensis, 2023)
Reseña del libro The Middle Voice and Connected Constructions in Ibero-Romance. A variationist and dialectal account